Moral Actions of The Characters in The Novel Selamat Tinggal By Tere Liye - Firnanda; Resdianto Permata Raharjo (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to describe the moral actions contained in the novel Selamat Selamat By Tere Liye using character education according to Thomas Lickona. Sources of data and research data are words, sentences, paragraphs and dialogue in the novel Selamat Selamat By Tere Liye. The method used in this research is a qualitative descriptive method. The focus of this research is on the moral actions of the characters in the novel Selamat Selamat by Tere Liye. The data collection method uses reading and note-taking techniques. The content analysis method is used as a data analysis method. The moral actions of the characters in the novel reflect the findings of this research as follows: (a) competence, (b) desires, and (c) habits. The results of this research can provide information that is useful for society in improving moral actions and can help the government in making policies regarding the cultivation of character education in the form of moral actions in society in Indonesia, and it is hoped that this research can significantly advance scientific understanding and improve the quality of human life.